(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
in today’s article Surgery or Chirurgia (Greek: chair - hand and ergon - movement, work), surgery - a branch of medicine. He studies diseases that require surgical operations and develops methods of operation. Since ancient times, people have helped themselves or each other by using simple methods such as applying pressure to the wound and sprinkling ashes on the wounds to stop the bleeding.